Congenital Toxoplasmosis: A Plea for a Neglected Disease - Wallon, Martine (Pathogens, 2018)
Maternal infection by Toxoplasma gondii during pregnancy may have serious consequences for the fetus, ranging from miscarriage, central nervous system involvement, retinochoroiditis, or subclinical infection at birth with a risk of late onset of ocular diseases. As infection in pregnant women is usually symptomless, the diagnosis relies only on serological tests. Some countries like France and Austria have organized a regular serological testing of pregnant women, some others have no prenatal program of surveillance. Reasons for these discrepant attitudes are many and debatable. Among them are the efficacy of antenatal treatment and cost-effectiveness of such a program. A significant body of data demonstrated that rapid onset of treatment after maternal infection reduces the risk and severity of fetal infection. Recent cost-effectiveness studies support regular screening. This lack of consensus put both pregnant women and care providers in a difficult situation. Another reason why congenital toxoplasmosis is disregarded in some countries is the lack of precise information about its impact on the population. Precise estimations on the burden of the disease can be achieved by systematic screening that will avoid bias or underreporting of cases and provide a clear view of its outcome.